(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Sepsis is significant cause of mortality in intensive care units. Septic cardiomyopathy is a severe complication of sepsis, with the report prevalence from 10 to 70%. Despite the lack of the diagnostic criteria and therapeutic protocols, septic cardiomyopathy may be defined as depressed intrinsic contractility induced by sepsis. However, the significance of septic cardiomyopathy has not been adequately recognized, without comprehensive researchs on its diagnosis, prognosis, and guideline management. We report a clinical case of a 72-years-old male patient diagnosed with septic shock due to perforated gastric peritonitis. Postoperatively, the patient developed circulatory collapse and depressed left ventricular ejection fraction (EF 39%), unresponsive to fluid resuscitation, vasopressors, and standard medical treatments, resulting in death after 9 days of treatment. Through this case study, we aim to review the recent literature focusing on the diagnosis and treatments of septic cardiomyopathy. Conclusion: Echocardiography is the gold standard for diagnosing myocarditis secondary to systemic infection. We should consider this diagnosis and perform necessary investigations if hemodynamic instability is refractory to fluid resuscitation and vasopressors. Early diagnosis and appropriate treatment strategies based on current guidelines and emerging research are crucial.